Evaluation of core faculty development workshop: experience from Patan Academy of Health Sciences, Nepal - Joshi, Mili; Shrestha, Ira; Bhandary, Shital (Journal of Patan Academy of Health Sciences, 2016)
Introductions: Faculty development programs (FDP) is important to promote the core education principles/philosophies and instill the innovations planned and/or carried out in any educational program. Thus, Patan Academy of Health Sciences (PAHS) carries regular FDP in order to effectively implement and innovate curriculum, and assessment. Methods: Effectiveness of the workshop was assessed by validated questionnaire of FDP workshop on PBL in 2010 at School of Medicine PAHS. Paired t-test was used to test the differences between before and after scores on knowledge and application on various aspects of the program. Effect size was also calculated to determine the size of the difference between before and after the workshop. Results: There were 19 participants, 11 male and 8 female, mean age was 38.4 years. There was overall increase in mean scores for all 18 items. The overall mean score of knowledge and application increased after FDP. The knowledge and application scale among the participants in terms of their age, gender and discipline increased. The effect sizes were high (d>1.3) and moderately high (0.8<d<1.3) for most scores. Conclusions: The knowledge and application of participants after FDP increased on various aspects of health professions education in the areas of adult teaching-learning, feedback cycle and assessment as part of the formal curriculum. Journal of Patan Academy of Health Sciences. 2016 Dec;3(2):36-40